Analysing of government's fiscal behaviour in the EU member states through clustering procedure - Daniela Pîrvu; Amalia Dutu; Carmen Enachescu (UTMS Journal of Economics, 2019)
The typical behaviour of EU Member States over the past decades has been to spend more public money than revenue earned by the government to finance programs with more or less important impact on society. Budget deficits and public debt have become important issues for EU countries, especially since a common currency, combined with very different tax regimes, can give rise to dangerous and unfair behaviours. The study proposes a new research technique for the fiscal behaviour of EU Member States. In the first stage of the research, a number of variables related to structural imbalances were defined. We assumed that EU Member States can be grouped into clusters according to these variables by which we characterize disciplined or undisciplined fiscal behaviour. We used Kmeans cluster analysis in order to establish if there are some clear patterns of fiscal behaviour among EU members. The research findings indicate that the research technique for the fiscal behaviour of Member States we proposed might be developed so as to allow identifying the Member States facing or likely to face problems in terms of public finances sustainability.
Keywords: E62; H60; 330; election cycle; fiscal sustainability; Kmeans cluster analysis